Systematic Review and Meta-Analysis of Psychosocial Risk Factors for Stroke - Lightbody, C. Elizabeth; Clegg, Andrew; Patel, Kulsum; Lucas, Julie Cook; Storey, Hannah; Hackett, Maree L.; Watkins, Dame Caroline L. (Seminars in Neurology, 2017)
Several studies have assessed the link between psychosocial risk factors and stroke; however, the results were inconsistent. We have conducted a systemic review and meta-analysis of cohort or case-control studies to ascertain the association between psychosocial risk factors (psychological, vocational, behavioral, interpersonal, and neuropsychological) and the risk of stroke. Systematic searches were undertaken in MEDLINE, EMBASE, CINAHL, PsycINFO, and the Cochrane Database of Systematic Reviews between 2000 and January 2017. Two reviewers independently screened titles, abstracts, and full texts. One reviewer assessed quality and extracted data, which was checked by a second reviewer. For studies that reported risk estimates, a meta-analysis was performed. We identified 41 cohort studies and 5 case-control studies. No neuropsychological papers were found. Overall, pooled adjusted estimates showed that all other psychosocial risk factors were independent risk factors for stroke. Psychological factors increased the risk of stroke by 39% (hazard ratio [HR], 1.39; 95% confidence interval [CI], 1.27–1.51), vocational by 35% (HR, 1.35; 95% CI, 1.20–1.51), and interpersonal by 16% (HR, 1.16; 95% CI, 1.03–1.31), and the effects of behavioral factors were equivocal (HR, 0.94; 95% CI, 0.20–4.31). The meta-analyses were affected by heterogeneity. Psychosocial risk factors are associated with an increased risk of stroke.
Keywords: stroke; psychosocial; risk factor